1978
DOI: 10.1111/j.1479-828x.1978.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Control of Ovarian Function — Concepts Derived from Gonadotrophin Therapy

Abstract: From experience gained in the monitoring of ovarian responses to gonadotropin therapy, it has been possible to develop concepts concerning the mechanisms which operate during the normal menstrual cycle. It is shown that the ovarian requirement for FSH operates in a very narrow range, involving changes in concentration of only 10%; this range operates from a threshold level, through an intermediate level to a maximum level. After adequate stimulation, the follicle goes through a costing phase during which it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
124
0
3

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(135 citation statements)
references
References 13 publications
8
124
0
3
Order By: Relevance
“…This study, also, suggested that both polymorphisms contribute to the individual variation in the FSH "threshold" [18]. This concept was initially introduced by Brown [19] and now constitutes the basis for gonadotropin administration in controlled ovarian stimulation (COS) in order to achieve multiple follicular growth [20,21]. The maintenance of follicles' growth in order to reach the pre-ovulatory stage depends on whether FSH levels surpass a distinct concentration (FSH "threshold") or not.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This study, also, suggested that both polymorphisms contribute to the individual variation in the FSH "threshold" [18]. This concept was initially introduced by Brown [19] and now constitutes the basis for gonadotropin administration in controlled ovarian stimulation (COS) in order to achieve multiple follicular growth [20,21]. The maintenance of follicles' growth in order to reach the pre-ovulatory stage depends on whether FSH levels surpass a distinct concentration (FSH "threshold") or not.…”
mentioning
confidence: 97%
“…In women, AMH is produced exclusively in the ovary by the granulosa cells of pre-antral and small antral follicles. The gene for AMH is located on chromosome 19 and consists of 5 exons [9,10]. The expression pattern of AMH seems to be similar in mice and human ovary.…”
mentioning
confidence: 99%
“…During the menstrual cycle, preantral follicles that encompass developing oocytes mature to a preovulatory stage in response to elevated levels of FSH (4). Administration of exogenous FSH also restores follicle development in anovulatory women (5). Finally, mice harboring null alleles for either the FSH receptor or FSH␤ lack preovulatory follicles and are infertile (6,7).…”
mentioning
confidence: 99%
“…This suggests that there are qualitative differences in the hormones (Wide, 1985) or that the number of follicles ovulating is mediated through influences other than the gonadotrophins. However, the radioimmunoassays (RIAs) used to measure FSH and LH may have been insensitive to the relatively small increases in gonadotrophin concentrations required to cause an increase in ovulation rate (Brown, 1978 (Davis et al, 1982).…”
Section: Introductionmentioning
confidence: 99%